Giant Darier–Ferrand dermatofibrosarcoma protuberans of the abdomen and pelvis: a case report - Triki, A. (J Med Case Rep, 2021)
BACKGROUND: Darier–Ferrand dermatofibrosarcoma (DFS) is a rare malignant cutaneous neoplasm characterized by local aggressiveness, high risk of recurrence, and low metastatic potential. CASE PRESENTATION: A 60-year-old Tunisian man with recurrent abdominopelvic DFS for which he had undergone multiple excisions presented with an extensive DFS that invaded the external genitals. He underwent a large excision with emasculation and thin cutaneous graft of the abdominal wall and local skin flap in the pelvis. CONCLUSION: DFS is a rare yet recurrent skin tumor. Wide excision with free margins remains the cornerstone of treatment. We report a case of a giant DFS treated with wide excision and reconstructive surgery to cover the defect.